PEMANFAATAN ZEOLIT PADA SUMUR RESAPAN AIR HUJAN UNTUK MENGURANGI RESIKO PENCEMARAN AIR TANAH AKIBAT LIMPASAN HUJAN UNTUK PENGEMBANGAN SNI 06-2459-2002 - Irianto, Eko Winar (JURNAL SUMBER DAYA AIR, 2018)
Groundwater recharge technology is the effort to reduce excessive surface runoff and to conserve the groundwater as well. However, runoff can disperse the pollutants which then accumulate in water bodies. Hence, pollutants can contaminate the groundwater by polluted surface runoff that enters the absorption well which is regarded as the most appropriate technology for water conservation. The objective of research is to know the capability of zeolit absorbing pollutants accumulated in the surface runoff. A prototype of absorption well for conserving and minimizing the risk of groundwater contamination is proposed in this research. Results of the research show that zeolit can reduce the pollutants dissolved in surface runoff. Thus, this material can be combined to the absorption well. This prototype should be built with local materials and will be proposed to improve the specification of the absorption well registered in SNI 06-2459-2002.